Influence of Erbium Ions on the Optical and Structural Properties of Polyvinyl Alcohol - Taymour A. Hamdalla; Taha A. Hanafy; Ashraf E. Bekheet (Journal of Spectroscopy)
Polyvinyl alcohol (PVA) films doped with erbium chloride (ErCl3) have been prepared by casting from their aqueous solutions. The structure of the doped samples as well as the interactions between the host PVA and Er+3 was investigated using FTIR spectroscopy. The optical measurement was recorded at room temperature in the range from 200 nm to 2000 nm. FTIR measurements revealed that Er+3 forms complex configuration within the PVA structure. PVA doped with 9 wt% of ErCl3 exhibits energy gap and refractive index of 5.1 eV and 1.72, respectively. The effect of the doping increment of ErCl3 on the optical parameters has been discussed.